2019
DOI: 10.1016/j.onehlt.2019.100093
|View full text |Cite
|
Sign up to set email alerts
|

Assessing health systems in Guinea for prevention and control of priority zoonotic diseases: A One Health approach

Abstract: To guide One Health capacity building efforts in the Republic of Guinea in the wake of the 2014–2016 Ebola virus disease (EVD) outbreak, we sought to identify and assess the existing systems and structures for zoonotic disease detection and control. We partnered with the government ministries responsible for human, animal, and environmental health to identify a list of zoonotic diseases – rabies, anthrax, brucellosis, viral hemorrhagic fevers, trypanosomiasis and highly pathogenic avian influenza – as the coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…The Guinea study found that coordination, training, infrastructure, public awareness and research were the main gaps and challenges. 44 Although the methodology is similar that study was more systems focused; broadly speaking it shows an overlap with our research themes.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The Guinea study found that coordination, training, infrastructure, public awareness and research were the main gaps and challenges. 44 Although the methodology is similar that study was more systems focused; broadly speaking it shows an overlap with our research themes.…”
Section: Discussionmentioning
confidence: 88%
“… 43 Meanwhile, a health systems study for prevention and control of zoonoses in Guinea found rabies, anthrax, brucellosis, viral haemorrhagic fevers, trypanosomiasis and highly pathogenic avian influenza as the country's top priority zoonoses and used these zoonoses as case studies to evaluate existing processes for prevention and control. 44 In Ethiopia, rabies, anthrax, brucellosis, leptospirosis and echinococcosis were considered the top priorities, and that additional public health and veterinary laboratory enhancement, along with intersectoral (human and animal health) linkages, were needed. 38 A network mapping study in Jordan found that while there is informal communication and effective coordination across the Ministry of Health and Ministry of Agriculture in the event of the emergence of one of the priority zoonoses studied, routine formal coordination is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to institutionalize these One Health linkages to ensure continuity and enable initiation of preparedness and response activities in a timely fashion when the next disease threat inevitably emerges. This need for improved communications across the multiple sectors of human, animal, environmental and economic well-being, has been highlighted as a major lacuna by multiple priority-setting exercises undertaken globally 44 45 .…”
Section: One Health Approach and Emerging Infectious Disease Threatsmentioning
confidence: 99%
“…Serological diagnosis indicative of schistosomiasis is connected to hypereosinophilia, approximately three weeks past the onset of the symptomatology [15]. Hypereosinophilia is characteristic of infection; however, there is a belated onset of eosinophilia in comparison to the outward show of symptoms [14].…”
Section: Diagnosis Of Trypanosomiasismentioning
confidence: 99%
“…Identification of the meiotic life cycle stage of Trypanosoma in the blood and lymphatic frameworks reveals side effects including irregular fever, lymphadenopathy, pruritus and specifi c profound agony vibrations. There is also an expression of slight neurological and hormone-related unsettling infl uences which are further indications of sensory system inclusion and, together with an extreme cerebral pain, this is a sign of transition to the second stage of the ailment [6,15]. Subsequently, sleep disorderliness affect circadian rhythms.…”
Section: Management Strategiesmentioning
confidence: 99%